A.N. Tolstoy’s Notebooks: From the Document to the Text of the Novel Peter the Great - Anna S. Akimova (Studia Litterarum)
A.N. Tolstoy worked on the novel Peter the Great for over 15 years, from 1929 to 1945. The writer admitted that the creation of a historical work about the era of Peter I was preceded by thorough preparation, which was associated with the accumulation of material, the study of historical sources, and attempts to use the language of that time in short stories. The article examines Tolstoy’s notebooks which testify to the writer’s long work on the language of the work and contain extracts from historical works, names and features of the characters, plans and sketches of chapters and individual scenes, as well as words and phrases. A.V. Alpatov was the first who attempted to use notebooks when commenting on the novel. Subsequently, he published materials for the book under the title From A. Tolstoy’s Notebooks to Peter the Great in the appendix to his monograph. Notebooks from the 1910s associated with the beginning of Tolstoy’s work on Peter’s epoch remained out of the researcher’s field of view.